When a patient's ethnicity is declared, medical students' decision‐making processes are affected. Issue 8 (August 2015) - Ewen, S. C.; Barrett, J.; Paul, D.; Askew, D.; Webb, G.; Wilkin, A.
Abstract Background Disparity in health status and healthcare outcomes is widespread and well known. This holds true for Indigenous peoples in many settings including Australia and Hawaii. While multi‐factorial, there is increasing evidence of health practitioner contribution to this disparity. This research explored senior medical students' clinical decision‐making processes. Methods A qualitative study was conducted in 2014 with 30 final year medical students from The University of Melbourne, Australia, and The John Burns Medical School, Hawaii, USA. Each student responded to questions about a paper‐based case, first in writing and elaborated further in an interview. Half the students were given a case of a patient whose ethnicity was not declared; the other half considered the patient who was Native Hawaiian or Australian Aboriginal. A systematic thematic analysis of the interview transcripts was conducted. Results The study detected subtle biases in students' ways of talking about the Indigenous person and their anticipation of interacting with her as a patient. Four main themes emerged from the interview transcripts: the patient as a person; constructions of the person as patient; patient–student/doctor interactions; and the value of various education settings. There was a strong commitment to the patient's agenda and to the element of trust in the doctor–patient interaction. Conclusion These findings will help to advance medical curricula so that institutions graduate physicians who are increasingly able to contribute to equitable outcomes for all patients in their care. The study also draws attention to subtle biases based on ethnicity that may be currently at play in physicians' practices.